Metabolic performance of the coral reef fish Siganus guttatus exposed to combinations of water borne diesel, an anionic surfactant and elevated temperature in Indonesia. Issue 2 (30th September 2016) - Baum, G.; Kegler, P.; Scholz-Böttcher, B.M.; Alfiansah, Y.R.; Abrar, M.; Kunzmann, A.
Abstract: Jakarta Bay in Indonesia and its offshore island chain, the Thousand Islands, are facing extreme pollution. Surfactants and diesel-borne compounds from sewage and bilge water discharges are common pollutants. However, knowledge of their effects on reef fish physiology is scarce. This study investigated combined and single effects of a) the water accommodated fraction of diesel (WAF-D, determined by ƩEPA polycyclic aromatic hydrocarbons (PAHs)) and b) the surfactant linear alkylbenzene sulfonate (LAS) on metabolic performance of the coral reef fish Siganus guttatus . Responses to combinations of each pollutant with elevated temperature (+ 3 °C) were determined. Short-term exposure to WAF-D led to a significant decrease in standard metabolic rates, while LAS led to an increase. During combined exposure, metabolic depression was observed. Effects of pollutants were not amplified by elevated temperature. This study highlights the need to reduce import of these pollutants and to avoid negative long-term effects on fish health. Highlights: Surfactants and diesel-borne compounds were determined in Jakarta Bay and the Thousand Islands. Exposure of Siganus guttatus to water accommodated fraction of diesel led to metabolic depression. Exposure of Siganus guttatus to an anionic surfactant led to increased metabolic rates. Combined exposure to both pollutants caused metabolic depression (interactive effect). Effects of pollutants were not amplified by elevated temperature (no synergism).